Identification characteristics of non-smoking tobacco products - S. V. Kalashnikov; M. V. Shkidyuk (Новые технологии, 2021)
Modern trends in the reduction of cigarette consumption have led to the spread of smokeless tobacco and non-tobacco nicotine-containing products [1]; their variety creates certain problems with the identification of products in this segment. Sucking tobacco (snus) has been banned in the Russian Federation for wholesale and retail trade since 2015, but it is a product similar to chew- ing tobacco in packaging, ingredient composition and physiological effects. Therefore, establishing the identification characteristics of chewing tobacco is an urgent task. The attitude towards chewing tobacco is controversial. The absence of the smoldering / burning process characteristic of cigarettes indicates a decrease in the harmful effect on the human body. At the same time, the physiological ef- fect on the consumer is based on the effect of nicotine extracted from tobacco through the oral mucosa. Consumer indicators of samples of smokeless tobacco / non-tobacco nicotine-containing products have been investigated: moisture content, fractional composition and nicotine content. The moisture content of samples of non-smoking products ranges from 19,0 % to 36,5 %. The nicotine content in the investigated tobacco / non-tobacco products is 0,3–2,4 % / 1,0–8,8 % respectively. To establish the identification signs of smokeless tobacco products the following methods have been used: product fractionation, optical microscopy, spectrophotometry, and liquid chromatography / tandem mass spectrometry (LCMS / MS). The main feature of the difference between smokeless tobacco products and non-tobacco nicotine-containing products has been determined – the presence of tobacco in the ingredient composition, confirmed by the structure of the product and the content of specific tobacco nitrosamines. As a result of the research, experimental data were obtained on the quantitative determination of the content of tobacco specific nitrosamines by the LCMS / MS method in smokeless tobacco products. The main identification feature of chewing tobacco has been established: the presence of raw tobacco in the ingredient composition with a coarse fraction content is at least 15 %.